Solubility, structural properties, and immunomodulatory activities of rice dreg protein modified with sodium alginate under microwave heating. Issue 8 (15th July 2019) - Meng, Xiangyong; Li, Tingting; Song, Teng; Chen, Chang; Venkitasamy, Chandrasekar; Pan, Zhongli; Zhang, Huien
Abstract: This research aims to investigate the solubility, structural properties, and immunomodulatory of rice dreg protein (RDP) modified with sodium alginate. The modification was done by wet heating assisted with microwave treatment. The solubility, emulsifying properties at pH 2–12, amino acid composition, molecular weight distribution, circular dichroism (CD) spectroscopy, and FTIR spectra of modified RDP were analyzed and discussed. Results showed that Maillard reaction could significantly enhance the solubility and emulsifying capacity of RDP. Further, an animal model for cyclophosphamide‐induced immunodeficiency was designed to evaluate the immunomodulatory effect of modified RDP. It is therefore suggested that modified RDP could improve the immunomodulatory effect of immunosuppressed mice, and the immunomodulation was concentration dependent, being generally enhanced by increased concentrations. This research revealed that glycosylation modification of RDP through Maillard reaction by wet heating assisted with microwave treatment may be successfully applied to improve the physicochemical properties and bioactive benefits of the final product. Abstract : This research aims to investigate the solubility, structural properties, and immunomodulatory of rice dreg protein (RDP) modified with sodium alginate. Based on structural analysis, the amino groups of RDP can be reacted with the reducing‐end carbonyl groups of sodium alginate, leading to unfolding and conformational flexibility of RDP and spatial structure changes and consequently improved solubility and emulsifying capacity of RDP grafted with sodium alginate. Furthermore, it can be concluded from the results that RDP grafted with sodium alginate had strong immunomodulatory properties, and the immunomodulation was concentration dependent, being generally enhanced by increased concentrations.